2019
DOI: 10.1017/wet.2019.18
|View full text |Cite
|
Sign up to set email alerts
|

Critical time for weed removal in glyphosate-resistant soybean as influenced by preemergence herbicides

Abstract: Widespread and repeated use of glyphosate resulted in an increase in glyphosate-resistant (GR) weeds. This led to an urgent need for diversification of weed control programs and use of PRE herbicides with alternative sites of action. Field experiments were conducted over a 4-yr period (2015 to 2018) across three locations in Nebraska to evaluate the effects of PRE-applied herbicides on critical time for weed removal (CTWR) in GR soybean. The studies were laid out in a split-plot arrangement with herbicide regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 24 publications
(27 reference statements)
2
22
0
3
Order By: Relevance
“…Corn at the V10 growth stage is near canopy closure depending on the row spacing and thus would substantially reduce the competitive impact of emerging weeds on grain yield (Knezevic et al 2003;Tursun et al 2016). Results from previous studies suggested that the CTWR varied with season, crop type, agronomic practice, and environmental factors (Adigun et al 2014;Evans et al 2003;Hall et al 1992;Knezevic et al 2019b;Norsworthy and Oliveira 2004; (Barnes et al 2019).…”
Section: Corn Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Corn at the V10 growth stage is near canopy closure depending on the row spacing and thus would substantially reduce the competitive impact of emerging weeds on grain yield (Knezevic et al 2003;Tursun et al 2016). Results from previous studies suggested that the CTWR varied with season, crop type, agronomic practice, and environmental factors (Adigun et al 2014;Evans et al 2003;Hall et al 1992;Knezevic et al 2019b;Norsworthy and Oliveira 2004; (Barnes et al 2019).…”
Section: Corn Yieldmentioning
confidence: 99%
“…Previous studies estimating CTWR in crops have demonstrated that the CTWR is location specific and can be influenced by crop type, weed composition and density, agronomic practices, and environmental conditions (Adigun et al 2014;Evans et al 2003;Knezevic et al 2019b;Osipitan et al 2016;Teasdale 1995;Tursun et al 2016). Limited studies have demonstrated how preplant and PRE herbicides could influence the CTWR and delay the need for POST weed control input in popcorn, soybean, and sunflower (Barnes et al 2019;Elezovic et al 2012;Knezevic et al 2019b). Barnes et al (2019) reported that CTWR started at the V10 or V15 stage with a PRE application of atrazine/S-metolachlor, compared to a CTWR at V4 when no PRE herbicide was used in popcorn.…”
Section: Introductionmentioning
confidence: 99%
“…In absence of a PRE herbicide, the ED 50 occurred at 205 GDDc, and it was delayed to 304 and 328 GDDc, respectively, with flumioxazin and flumioxazin/metribuzin/pyroxasulfone. Similarly, Knezevic et al (2019) reported that saflufenacil/imazethapyr/pyroxasulfone and sulfentrazone/imazethapyr applied PRE delayed the ED 50 to 699 and 850 GDDc, respectively, compared with 222 GDDc when no PRE herbicide was applied, with common weed species across the research sites being common lambsquarters (Chenopodium album L.), velvetleaf (Abutilon theophrasti Medik. ), and waterhemp [Amaranthus tuberculatus (Moq.)…”
Section: Soybean Yield Componentsmentioning
confidence: 82%
“…where Y is the response variable (yield [kg ha -1 ], plants m -1 row, pods plant -1 , seeds pod -1 , or yield loss [YL]), c is the lower limit, d is the upper limit, x is the duration of weed removal timing in GDDc, e is the ED 50 (GDDc where 50% response between lower and upper limit occurs; inflection point), and b is the slope of the line at the inflection point. The CTWR in this study was determined based on an arbitrary 5% yield loss threshold (Knezevic et al, 2003(Knezevic et al, , 2019. Root mean square error and modeling efficiency (ME) were calculated to evaluate goodness of fit for soybean yield and yield loss (Barnes et al, 2018;Roman et al, 2000;Sarangi & Jhala, 2018b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation